Chemical and biological methods to detect post‐translational modifications of arginine. Issue 2 (25th November 2013) - Slade, Daniel J.; Subramanian, Venkataraman; Fuhrmann, Jakob; Thompson, Paul R.; Martin, Brent R.; Martin, Brent R.
ABSTRACT Post‐translational modifications (PTMs) of protein embedded arginines are increasingly being recognized as playing an important role in both prokaryotic and eukaryotic biology, and it is now clear that these PTMs modulate a number of cellular processes including DNA binding, gene transcription, protein–protein interactions, immune system activation, and proteolysis. There are currently four known enzymatic PTMs of arginine (i.e., citrullination, methylation, phosphorylation, and ADP‐ribosylation), and two non‐enzymatic PTMs [i.e., carbonylation, advanced glycation end‐products (AGEs)]. Enzymatic modification of arginine is tightly controlled during normal cellular function, and can be drastically altered in response to various second messengers and in different disease states. Non‐enzymatic arginine modifications are associated with a loss of metabolite regulation during normal human aging. This abnormally large number of modifications to a single amino acid creates a diverse set of structural perturbations that can lead to altered biological responses. While the biological role of methylation has been the most extensively characterized of the arginine PTMs, recent advances have shown that the once obscure modification known as citrullination is involved in the onset and progression of inflammatory diseases and cancer. This review will highlight the reported arginine PTMs and their methods of detection, with a focus on new chemical methods to detect protein citrullination. © 2013 Wiley Periodicals, Inc. Biopolymers 101: 133–143, 2014.